Toll-like Receptor 1 Polymorphisms Affect Innate Immune Responses and Outcomes in Sepsis - Wurfel, Mark M; Gordon, Anthony C; Holden, Tarah D; Radella, Frank; Strout, Jeanna; Kajikawa, Osamu; Ruzinski, John T; Rona, Gail; Black, R. Anthony; Stratton, Seth; Jarvik, Gail P; Hajjar, Adeline M; et al. (American journal of respiratory and critical care medicine, 2008)
Polymorphisms affecting Toll-like receptor (TLR)-mediated responses could predispose to excessive inflammation during an infection and contribute to an increased risk for poor outcomes in patients with sepsis. To identify hypermorphic polymorphisms causing elevated TLR-mediated innate immune cytokine and chemokine responses and to test whether these polymorphisms are associated with increased susceptibility to death, organ dysfunction, and infections in patients with sepsis. We screened single-nucleotide polymorphisms (SNPs) in 43 TLR-related genes to identify variants affecting TLR-mediated inflammatory responses in blood from healthy volunteers ex vivo. The SNP associated most strongly with hypermorphic responses was tested for associations with death, organ dysfunction, and type of infection in two studies: a nested case-control study in a cohort of intensive care unit patients with sepsis, and a case-control study using patients with sepsis, patients with sepsis-related acute lung injury, and healthy control subjects. The SNP demonstrating the most hypermorphic effect was the G allele of TLR1(-7202A/G) (rs5743551), which associated with elevated TLR1-mediated cytokine production (P < 2 x 10(-20)). TLR1(-7202G) marked a coding SNP that causes higher TLR1-induced NF-kappaB activation and higher cell surface TLR1 expression. In the cohort of patients with sepsis TLR1(-7202G) predicted worse organ dysfunction and death (odds ratio, 1.82; 95% confidence interval, 1.07-3.09). In the case-control study TLR1(-7202G) was associated with sepsis-related acute lung injury (odds ratio, 3.40; 95% confidence interval, 1.59-7.27). TLR1(-7202G) also associated with a higher prevalence of gram-positive cultures in both clinical studies. Hypermorphic genetic variation in TLR1 is associated with increased susceptibility to organ dysfunction, death, and gram-positive infection in sepsis.